1998
DOI: 10.1016/s0194-5998(98)70266-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Cervical Tuberculosis in Patients with HIV Infection

Abstract: These data suggest that tuberculosis should be considered in the differential diagnosis of all head and neck lesions in patients infected with HIV, even in the absence of pulmonary involvement. Purified protein derivative testing should be done liberally in these patients, with realization that the sensitivity of purified protein derivative testing is reduced in patients with AIDS. Fine-needle aspiration biopsy should be the key diagnostic test in this patient population, with open surgical biopsy reserved for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
12
0
5
Order By: Relevance
“…The majority of the studies reported on ethnicity and constitutional symptoms ( n = 9). In 8 studies, there was information on HIV infection of which 1 study solely included HIV patients [25]. Three studies reported other comorbidities than HIV [20, 26, 29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the studies reported on ethnicity and constitutional symptoms ( n = 9). In 8 studies, there was information on HIV infection of which 1 study solely included HIV patients [25]. Three studies reported other comorbidities than HIV [20, 26, 29].…”
Section: Resultsmentioning
confidence: 99%
“…Five articles had data on patient delay [20, 22-25], three on health care delay [19, 26, 27], and three on total delay [21, 28, 29]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations